Designing a family health nursing online course: Weaving accessible pedagogy approaches - Epstein, Iris; Ord-Lawson, Susan Elizabeth (Advances in Social Sciences Research Journal, 2018)
We are writing this paper to report on students’ and faculty experiences in an online family nursing health course based on 'relational inquiry', that is, a way of thinking that situates individuals within their cultural and social context. Research shows a gap exists between what nursing students are taught and what they later find out nursing really is. In addition, with the increased use of online nursing core courses in the curriculum, facilitating accessability and engaging the diverse learner in the complex nursing realities can be even more challenging. During the last 5 years, we have been teaching a family health assessment course using Doane and Varcoe’s (2015) relational inquiry concepts for Registered Practical Nurses (RPN) bridging to a Bachelor of science in Nursing (BScN). Teaching relational inquiry concepts fully online has been challenging in terms of helping the diverse learner access and navigate the complex nursing workplace realities and form a virtual relationship with self, peers, faculty, and the online environment. Through the use of families’ who are situated in diverse culture and context, relational inquiry acknowledges nurses’ workplace realities and then offers students ways to navigate this complexity. Thus, the purpose of this paper is to describe four accessible pedagogy approaches we included in our online course (e.g., creating a video or transcript; posting or replying to an article; joining a synchronized discussion; and participating in a non-synchronized discussion) and report students’ and faculty experiences from a relational inquiry lens.